ASSESSMENT OF LOAN TO DEPOSIT RATIO SOE BANK (PERSERO) BASED ON FINANCIAL RATIO - Lidiawan, Angga Rizka (Program Doktor Ilmu Ekonomi, 2022)
This study was conducted to examine the effect of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM) on Loan to Deposit Ratio (LDR). The research object of the State-Owned Enterprise Bank and the research data variables are sourced from financial reports that have been published and accessed through their respective web addresses. The data analysis technique used multiple linear regression with least squares equation and hypothesis testing using t-statistics to test the partial regression coefficients and F-statistics to test the significance of the effect together with a significance level of 5%. In addition, the classical assumption test was also carried out which included normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The results showed that the NIM variable showed a significant effect on LDR. The NPL variable has a significant negative effect on LDR. The CAR variable has a positive but not significant effect on LDR. The predictive ability of these three variables on the LDR in this study was 51.1%, while the remaining 48.9% was influenced by other factors that were not included in the research model. Keywords : Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Non Perfoming Loan (NPL), Net Interest Margin (NIM)